The conundrum of the connection of grapevine Pinot gris virus with the grapevine leaf mottling and deformation syndrome. (19th November 2022) - Tarquini, Giulia; Ermacora, Paolo; Martini, Marta; Firrao, Giuseppe
Abstract: Since its discovery in 2012, the role of the trichovirus named grapevine Pinot gris virus (GPGV) as the causative agent of grapevine leaf mottling and deformation (GMLD) syndrome, a grapevine disease for which symptoms had been observed in north Italy and western Slovenia a few years earlier, has been a matter of discussion. In the following 10 years of investigations, evidence has emerged of a role for the genetic diversity of the virus and for the varietal diversity of the host, as well as their interaction during antiviral defence (i.e. RNA silencing) and virus‐mediated defence suppression. In a context of wider research efforts, several relevant aspects of GPGV evolution and GMLD epidemiology were also clarified. Nevertheless, a complete understanding of the molecular events and the environmental conditions that could affect viral infection severity and symptom display remains a challenging puzzle. In the meantime, we are witnessing a large spread of the virus, which has almost completely permeated the regions where it first appeared, while spreading through most areas of grapevine cultivation. A deeper knowledge of the molecular context of the disease is key to establishing whether the impressive potential of GPGV to spread makes it a candidate as the next emerging threat for the grapevine industry. Abstract : How complex is the GPGV–GMLD enigma? A review of 10 years of efforts to highlight players and roles.